CD25 as a unique marker on human basophils in stable-mildly symptomatic allergic asthma - Iype, Joseena; Rohner, Lionel; Bachmann, Sofia; Hermann, Tanja Rahel; Pavlov, Nikolay; von Garnier, Christophe; Fux, Michaela (Frontiers in Immunology, 2023)
Basophils in acute asthma exacerbation are activated as evidenced by their increased expression levels of activation markers such as CD203c and CD63. However, whether basophils of allergic asthmatics who are in stable phase and have no asthma exacerbations display a specific and distinctive phenotype from those of healthy individuals has yet to be well characterized. We aimed to identify the phenotype of basophils from allergic asthmatics in the stable phase and investigate whether such a phenotype is affected by ex vivo allergen stimulation. We determined by flow cytometry, the expression of surface proteins such as CD25, CD32, CD63, CD69, CD203c, and CD300a and intracellular anti-apoptotic proteins BCL-2, BCL-xL, and MCL-1. We investigated these markers in blood basophils obtained from well-characterized patients with stable-mildly symptomatic form of allergic asthma with no asthma exacerbation and from healthy individuals. Moreover, we determined ex vivo CD63, CD69, and CD25 on blood basophils from stable-mildly symptomatic allergic asthmatics upon allergen stimulation. In contrast to all tested markers, CD25 was significantly increased on circulating basophils in the patient cohort with stable-mildly symptomatic allergic asthma than in healthy controls. The expression levels of CD25 on blood basophils showed a tendency to positively correlate with FeNO levels. Notably, CD25 expression was not affected by ex vivo allergen stimulation of blood basophils from stable-mildly symptomatic allergic asthma patients. Our data identifies CD25 as a unique marker on blood basophils of the stable phase of allergic asthma but not of asthma exacerbation as mimicked by ex vivo allergen stimulation.